Obscurants in Babylon. (1st October 2016) - Ivanova, Ekaterina
Abstract : Ekaterina Ivanova's article examines two novels that break the remaining taboo against positive depictions of Christianity in Russian science fiction and fantasy, The Obscurant (Mrakobes, 1994) by Elena Khaetsaia, and Ol'ga Chigirinskaia's Heart of the Sword (Serdtse mecha, 2006). After outlining the plots and main characters, she notes the grinding negative scenes the novels include and the potential effect on readers. At the same time, Ivanova sees these novels as evidence that authors are choosing to apply the language and methods of fantastika to the most difficult moral and religious questions.